2009
DOI: 10.1111/j.1095-8312.2008.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in stickleback head morphology associated with parasite infection

Abstract: Dingemanse, N. J., Oosterhof, C., Van Der Plas, F., Barber, I. (2009). Variation in stickleback head morphology associated with parasite infection. Biological Journal of the Linnean Society, 96, (4), 759-768. Sponsorship: Netherlands Organization for Scientific Research; Research Council of Norway IMPF: 02.04 RONO: 00Parasites can affect host phenotypes, influencing their ecology and evolution. Host morphological changes occurring post-infection might result from pathological by-products of infection, or repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…Parasites often affect head size and shape, even when they do not reside in the head itself. Cestode-infected fish exhibit smaller heads, and head size further decreased with increasing parasitic load (Dingemanse et al 2009). This pattern of increased morphological change in response to increased parasitic load has been previously observed in various systems (Krist 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasites often affect head size and shape, even when they do not reside in the head itself. Cestode-infected fish exhibit smaller heads, and head size further decreased with increasing parasitic load (Dingemanse et al 2009). This pattern of increased morphological change in response to increased parasitic load has been previously observed in various systems (Krist 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although host responses to infection are clearly common, it remains difficult to predict the direction they will take and the degree to which host and parasite will benefit from them (Dingemanse et al 2009). For example, body size can either increase or decrease in response to the parasite.…”
Section: Introductionmentioning
confidence: 99%
“…Parasites can affect host phenotypes, for example by causing a reduction in size and shape of heads of threespined sticklebacks (Dingemanse et al 2009a). Furthermore, parasites can increase selection against migrants between diversifying populations because migrants encounter parasites to which they are poorly adapted (Maccoll and Chapman 2010).…”
Section: Understudied Dimensions Of Niche Divergencementioning
confidence: 99%
“…The process of dynamic interactions between host and parasite can lead to host physiological and morphological changes (Johnson, 1999, Roberts et al., 1999, Tinsley et al., 2002, Kristan and Hammond, 2004, Dingemanse et al., 2009). Experimental studies with adult and young mice ( Mus musculus ) have shown that the intestinal nematode ( Heligmosomoides polygyrus ) decrease host body reserves (e.g.…”
Section: Introductionmentioning
confidence: 99%